Karakterisasi Pertumbuhan, Kandungan Pati, dan Kadar HCN Berbagai Klon Ubikayu (Manihot esculenta Crantz) - Negrita Anggraini; Erwin Yuliadi; Kukuh Setiawan; Muhammad Syamsoel Hadi (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2021)
This study was aimed to determine the qualitative character and evaluate starch content and HCN in six cassava clones. This research was conducted at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung from April 2018 to April 2019. This study used a Completely Randomized Block Design (CRBD) consisting of 2 replications. The cassava clones used consisted of Huay Bong, Waxy, Melati, Manalagi, Kuning, and Ketan Lokal. The variables observed were leaf color, stem color, tuber color, tuber length, tuber diameter, tuber weight, starch content, and HCN content. Data were analyzed using SAS (ver. 9.0). The results showed that there were no significant quantitative variables in the tuber diameter, tuber weight, and HCN content. Waxy clones has the highest levels of starch (12.72 %) and the highest levels of HCN (0.06 mg/g). Whereas Kuning clones has the lowest levels of starch  (5.72 %) and Melati clones has the lowest HCN levels (0.02 mg/g). In qualitative variables, each cassava clone has different qualitative characters, in the color variable of the tuber cortex, 4 consumption cassava clones consist of white (Melati, Manalagi, Kuning, and Ketan Lokal). Whereas in 2 tapioca industry cassava clones consisted of white (Huay Bong) and pink (Waxy).